1998
DOI: 10.1073/pnas.95.13.7637
|View full text |Cite
|
Sign up to set email alerts
|

A unified theory of carcinogenesis based on order–disorder transitions in DNA structure as studied in the human ovary and breast

Abstract: Fourier transform-infrared͞statistics models demonstrate that the malignant transformation of morphologically normal human ovarian and breast tissues involves the creation of a high degree of structural modification (disorder) in DNA, before restoration of order in distant metastases. Order-disorder transitions were revealed by methods including principal components analysis of infrared spectra in which DNA samples were represented by points in two-dimensional space. Differences between the geometric sizes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 29 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…In an attempt to answer this question, we used Fourier transform-infrared (FT-IR) spectroscopy with multivariate statistics to delineate structural differences between thin films of a 25-base DNA strand and comparable strands containing centrally located single G o and A o groups. FT-IR͞statistical analysis was previously used to study subtle changes in base and phospho-deoxyribose structures of DNA in relation to tumor progression (13)(14)(15)(16)(17)(18)(19). In the present study, a number of spectral differences attributable to base interactions and backbone conformations were identified between the 25-base parent strand and derivatives containing G o and A o substituents.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In an attempt to answer this question, we used Fourier transform-infrared (FT-IR) spectroscopy with multivariate statistics to delineate structural differences between thin films of a 25-base DNA strand and comparable strands containing centrally located single G o and A o groups. FT-IR͞statistical analysis was previously used to study subtle changes in base and phospho-deoxyribose structures of DNA in relation to tumor progression (13)(14)(15)(16)(17)(18)(19). In the present study, a number of spectral differences attributable to base interactions and backbone conformations were identified between the 25-base parent strand and derivatives containing G o and A o substituents.…”
mentioning
confidence: 82%
“…In this regard, FT-IR spectroscopy with multivariate statistics is known to be sensitive to subtle changes in the base and backbone structures of DNA in cancer-prone tissues and neoplasms [e.g., prostate (15) and breast (14,18,19)]. The FT-IR͞statistical approach is thus an attractive means for acquiring information on conformational and other changes in a variety of synthetic and natural DNA structures (17).…”
Section: Discussionmentioning
confidence: 99%
“…The Spearman correlation coefficients between base lesion concentrations and age were 0.52 (P ϭ 0.015) for 8-OH-Gua, 0.55 (P ϭ 0.01) for 8-OH-Ade, and 0.50 (P ϭ 0.02) for FapyGua. In a previous study (32), increased variance in mutagenic base lesions in tumor-prone tissues was hypothesized to be an obligatory precursor to clonal selection and subsequent tumor formation.…”
Section: Resultsmentioning
confidence: 99%
“…Results and Discussion MCA-Induced DNA Damage Before Tumor Formation. We have demonstrated that the FTIR statistical models of DNA used in this study are capable of identifying a variety of subtle changes in base functional group and backbone structures as well as alterations in conformational properties (20) associated with carcinogenesis (19,21,(23)(24)(25). Specifically, this technology has been used most recently to discriminate between DNA structures of normal prostate tissues, primary tumors, metastasizing primary tumors, and distant metastases of the prostate (18).…”
Section: Methodsmentioning
confidence: 99%
“…7, we investigated changes in DNA structure associated with MCA exposure. Fourier transforminfrared (FTIR) spectral models (17)(18)(19)(20)(21) were used to identify alterations in the nucleotide bases and phosphodiesterdeoxyribose backbone during tumorigenesis. Moreover, we looked for the early development of a DNA structure (cancer DNA phenotype), indistinguishable from that of tumor DNA, which was found in the prostates of older, cancer-free men (18).…”
mentioning
confidence: 99%